2018
DOI: 10.1002/path.5004
|View full text |Cite
|
Sign up to set email alerts
|

Blocking 17β‐hydroxysteroid dehydrogenase type 1 in endometrial cancer: a potential novel endocrine therapeutic approach

Abstract: The enzyme type 1 17β-hydroxysteroid dehydrogenase (17β-HSD-1), responsible for generating active 17β-estradiol (E2) from low-active estrone (E1), is overexpressed in endometrial cancer (EC), thus implicating an increased intra-tissue generation of E2 in this estrogen-dependent condition. In this study, we explored the possibility of inhibiting 17β-HSD-1 and impairing the generation of E2 from E1 in EC using in vitro, in vivo, and ex vivo models. We generated EC cell lines derived from the well-differentiated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…Preclinical studies on 17βHSD1 inhibitors showed promising results in a mouse model of endometrial hyperplasia (Saloniemi et al, 2010 ;Järvensivu et al, 2015 ) and in various models of EC (Konings et al, 2018 ).…”
Section: Intracrinology In Peripheral Tissuesmentioning
confidence: 99%
“…Preclinical studies on 17βHSD1 inhibitors showed promising results in a mouse model of endometrial hyperplasia (Saloniemi et al, 2010 ;Järvensivu et al, 2015 ) and in various models of EC (Konings et al, 2018 ).…”
Section: Intracrinology In Peripheral Tissuesmentioning
confidence: 99%
“…[ 32 ] We are currently noting an increasing number of studies on HSD17B1 inhibitors for the treatment of hormone‐dependent diseases, including endometriosis, breast cancers, and cervical cancer. [ 33–35 ] Most of the aforementioned hormone‐dependent diseases are associated with HSD17B1 overexpression, and inhibitors are being designed to compete for the active sites on the substrate or coenzyme. [ 36 ] Our competitive assays herein, however, did not show that LA acted on a region of the coenzyme or substrate.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent clinical trials indicate that the efficacy of hormonal drugs is improved if combined with other targeted treatments (see Section 3 ) [ 7 ]. Since ongoing pre-clinical research has already identified a number of additional novel endocrine targets [ 8 , 9 , 10 ], it can be envisaged that in the near future several endocrine targets and novel drugs will be available for various combinational regimens in EC clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of EC, pre-clinical models are based on in vitro 2D monolayer cell cultures, 3D spheroid cell cultures, and in vivo models using the chorioallantoic membrane assay (CAM) or by a subcutaneous injection of human EC cell lines in athymic mice. However, these models are suboptimal and often lack estrogen dependency and clear estrogen responses (see Section 3 ) [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%